Intestinal microbiom as a therapeutic target in treatment of chronic non-alcoholic fat liver disease - E. Yu. Plotnikova; Yu. V. Zakharova; T. Yu. Gracheva (Лечащий Врач)
While standard diets, changes in the way of life, and pathogenically oriented methods of treatment of non-alcoholic fat liver disease are often ineffective, it is necessary to develop new approaches aimed to other targets. Under the conditions of damaged intestinal barrier (“leaking bowel”), and bowel- liver axis, it is possible to improve natural interaction between the intestinal bacteria and peptic receptors, which contributes to the following course of events: oxidative stress, insulin-resistance, liver inflammation and fibrosis. The article also highlights possibility of intestinal microbiota modulation with probiotics.